Recovery of Silver and Lead from Jarosite Residues by Roasting and Reducing Pyrometallurgical Processes - Cancio Jiménez-Lugos; Manuel Flores-Favela; Antonio Romero-Serrano; Aurelio Hernández-Ramírez; Josué López-Rodríguez; Lorena Cuéllar-Herrera; Eduardo Colin-García (Metals, 2024)
This work focuses on the recovery of lead and silver from jarosite waste by a three-stage process: drying, roasting and reduction at 100 °C, 700 °C and 1400 °C, respectively. A flux mixture with 48 mass% CaO and 52% SiO2 was used for the reduction stage. A gas consisting of 70 vol% CO and 30 vol% CO2 was used as a reducing agent. To select the temperatures and the amount of flux and reducing agent, a characterization of the jarosite waste was carried out using thermogravimetry and high-temperature X-ray diffraction, as well as a thermodynamic study of the effects of the process parameters. The lead-rich metallic and slag phases were characterized by chemical analysis, SEM-EDS and XRD. In addition, the jarosite residue and the final slag were leached with an aqueous acetic acid solution to estimate their chemical stability. The results show a recovery of over 95% of the lead and silver and the formation of an environmentally friendly residual slag.